HUBUNGAN MODAL INTELEKTUAL DAN TATA KELOLA PERUSAHAAN TERHADAP PROFITABILITAS PERUSAHAAN MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA - Jannati Tangngisalu (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
This objectives this study are: (1) to determine and analyze the effect of intellectual capital on the profitability of food and beverage manufacturing companies on the Indonesia Stock Exchange, (2) to determine and analyze the effect of corporate governance on the profitability of food and beverage manufacturing companies on the Indonesia Stock Exchange. Data collection using secondary data with population is food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange from 2014 to 2016, as many as 16 companies. Sampling technique using purposive sampling with the number of companies that meet the criteria used as research samples as many as 11 companies with a period of 3 years. Hypothesis testing uses multiple linear regression analysis techniques with the help of SPSS version 22.00. The results of this study indicate that (1) intellectual capital has no effect and is not significant on profitability (2) corporate governance has no effect and is not significant on the profitability of food and beverage sector manufacturing companies on the Indonesia Stock Exchange.